Parkett : The Parkett series with contemporary artists. (Zürich : Parkett-Verlag, 1994)
Table of Content : Orozco in Paris by Claude Gintz Kasseböhmer’s Trees by Walter Grasskamp ; Felix Gonzalez-Torres Travelogue by Nancy Spector ; In Purgatory: The Work of Felix Gonzalez-Torres by Simon Watney ; Social Works by Susan Tallman Wolfgang Laib A Room by Wolfgang Laib ; in the Centre Pompidou by Didier Semin ; More than Myself by Clare Farrow ; A Waxroom in the Mountain by Jean-Marc Avrilla ; Medicine Man – Proposing a Context for Wolfgang Laib’s Work by Thoms McEvilley ; Roni Horn, Insert Matthew Barney’s Fornication with the Fabric of Space by Neville Wakefield ; Burt Barr, Les Infos du Paradis by Lynne Cooke In the Pool by Klaus Kertess ; Merde in France, Cumulus from Europe by Eric Troncy ; I Want to Be in America, Cumulus from America by Meyer Vaisman ; Reality as Forgery by Laura Arici
Like two purists who have put the heat on a traditionally cool domain, our collaboration artists in this issue—Felix Gonzalez-Torres (*1957) and Wolfgang Laib (*1950)—produce art that glows with precisely balanced gestures, subtly infiltrated signs, and cogent mental fields of force. Wolfgang Laib has chosen a spot in the Pyrenees, to form there a public place as a sanctuary of solitude, a place covered with "that energetic gold that is wax." (Jean-Marc Avrilla) (editorial by publisher)
boek
Keywords: Gonzalez-Torres, Felix; Laib, Wolfgang